RESEARCH ARTICLE: Representation of Fracking in Mainstream American Newspapers. (27th May 2016) - Habib, Sabrina; Hinojosa, Melanie Sberna
Abstract : This study employed deductive content analysis how hydraulic fracturing, also known as fracking, in online versions of elite American newspapers. The media sources The New York Times, Los Angeles Times, and The Washington Post were chosen as the best outlets to analyze to gain insight into the print and digital media that influence public opinion in the United States. A total of 349 articles published from 1851 to May 2014 were included in this study. The study instrument was based on previous media framing studies, including those on hydraulic fracturing and climate change communication, in addition to observations of patterns noted by the authors during an initial round of coding in the interest of relevance. This study examined the tone in which media coverage portrays hydraulic fracturing, thereby influencing social perceptions of the practice. Significant findings from the study are (a) hydraulic fracturing is presented by elite news outlets through conflict, responsibility (blame), and environmental concerns; and (b) water pollution was the main concern portrayed in the articles, which presents hydraulic fracturing mostly as a water-related issue while leaving out other important aspects of natural gas extraction. Environmental Practice 18: 83–93 (2016)